Cr(III)-Incorporated Fe(III) Hydroxides for Enhanced Redox Conversion of As(III) and Cr(VI) in Acidic Solution - Juanjuan Liu; Xubo* Gao; Chong Dai; Zhang, Suona; Shuqiong Kong; Lin Wang; Yandi* Hu (Environmental Science: Nano, 2025)
Impurity-containing iron hydroxides, abundant in many natural and engineered soil and aqueous environments, control the fate and transport of multiple aqueous contaminants. Fe(III) hydroxide was reported to simultaneously detoxicate As(III) and Cr(VI). However, the mechanisms and reaction intermediates are not clear, and the effects of impurities in ferrihydrite were far from being well understood. Here, Cr(III)-incorporated Fe(III) hydroxides were precipitated from acidic solutions (pH ∼ 3.0) with varied Fe(III)/Cr(III) molar ratios (10 : 0 to 8 : 2) for simultaneous removal of As(III) and Cr(VI). Multiple characterization techniques were combined to investigate the effects of Cr-incorporation on the size, band gap, adsorption, and catalytic efficiency of Fe hydroxides. With the amounts of Cr-incorporation increasing, the particle size of Fe hydroxides rapidly decreased (from 16.7 to 6.0 nm), and the removal of total As/Cr increased, as the Cr-incorporated Fe hydroxides with smaller size had larger surface area, promoting As/Cr removal by adsorption. Based on As/Cr speciation analysis of both aqueous and solid phases, the molar ratios of the oxidized As(III) (88%) to reduced Cr(VI) (∼56%) were calculated to be ∼1.5, indicating that the coupled redox conversion was the dominant removal mechanism over As(III)/Cr(VI) adsorption and As(III) oxidation. Intermediate characterization and molecular simulation found that Cr-incorporation promoted the early formation of H2O2 and Cr(V) intermediates, and enhanced the adsorption of reaction intermediates on Cr-incorporated Fe hydroxides, thus promoting their catalytic efficiency for coupled As(III)/Cr(VI) redox reactions.